ANALISIS PENDIDIKAN KARAKTER PADA ANAK USIA DINI MELALUI INTERAKSI SOSIAL DAN PENGENALAN NUMERASI SEJAK DINI - Cicik Fauziyah; Ruqoyyah Fitri; Yes Matheos Lasarus Malaikosa (Universitas Bhinneka PGRI, 2025)
This study aims to examine the application of character education in early childhood through social interaction and the introduction of counting. Character education at an early age is very important in shaping moral, ethical and social values that become the foundation of a child's personality. Through a qualitative method with a literature study approach, this research analyzes various findings regarding character education obtained from various related studies. The results show that character education can be strengthened through social interaction activities such as group games, collaborative projects and daily activities that involve values such as cooperation, responsibility and empathy. In addition, the early introduction of numeracy also plays a role in supporting children's character development, as numeracy teaches children to think critically, solve problems and work together in facing challenges. Project-based learning is proven to be effective in integrating numeracy and character. This study also found the importance of parents and teachers in supporting children's character development at home and at school. The conclusion of this study confirms that character education through social interaction and numeracy can create a generation that is smart, has integrity, and is ready to face life's challenges.